Green Coconut Water Stimulates Follicular Growth and Development in the Ovary of Hyperprolactin Sprague- Dawley (African Journal of Biomedical Research, 2019)
Hyperprolactinaemia is a common endocrine cause of infertility in women. It is essentially associated with decrease in the secretion of follicle stimulating hormone which consequently leads to the inhibition of follicular development. Green coconut water (GCW) is the liquid in the inner cavity of an immature coconut fruit. Studies have demonstrated that GCW has estrogenic property that can regulate the endocrine system. This present study therefore investigated the effects of GCW on follicular growth and development in hyperprolactine rats to determine its endocrine regulating property on ovarian folliculogenesis. A total of fifty- five cyclic female Sprague-Dawley rats weighing 145-170 g were used for this study. The animals were randomly divided into four experimental study groups. In group 1, Metoclopramide hydrochloride (MCH) at 0.2 mg/100 g body weight was administered daily for 28 days to induce hyperprolactinaemia and this was withdrawn for 8, 16 and 28 days to check for recovery. The animals in group 2 were post-treated with GCW. In group 3, animals were treated with GCW only and group 4, the control group received distilled water only. The ovaries were carefully dissected out, trimmed of fat and processed for histology with Haematoxylin & Eosin stains. The histological presentation of follicular growth and development pattern in the ovaries of the post-treatment groups were comparable with the control. Therefore, this study presented structural evidence that GCW stimulates follicular growth in the ovary of hyperprolactin rats.
Keywords: Ovary; Follicles; Histology; Green coconut water; hyperprolactinaemia